Relation between sum of skinfolds and systemic blood pressure in adolescents - Rodrigo Bozza; Valter Cordeiro Barbosa Filho; Renato Silva Barbosa Maziero; Maicon de Siqueira Bontorin; Wagner de Campos (Universidade de Fortaleza, 2014)
Objective: To relate the sum of skinfolds to systemic blood pressure in adolescents attending public schools. Methods: Cross-sectional study conducted with 543 adolescents from public schools of Curitiba-PR-Brazil, aged between 11 and 17 years, regardless of sex, in the period from August 2010 to June 2011. Body weight, height and skinfolds (triceps, subscapular, suprailiac, abdominal and calf) were measured. Systolic (SBP) and diastolic (DBP) blood pressure were determined by duplicate auscultatory method. A new evaluation was performed the day after the first collection in adolescents identified with pre-hypertension or hypertension. Partial correlation was used as a measure of association between variables, considering height and age as control variables. Analyses were stratified by sex and the level of significance was set at 5%. Results: Among male adolescents, the sum of skinfolds presented a correlation to SBP and DBP of 0.18 (p<0.01) and 0.14 (p<0.05), respectively. Among female adolescents, the correlation of the sum of skinfolds to SBP and DBP was 0.15 (p <0.01) and 0.19 (p <0.01), respectively. Of the total sample, 9.2% (n=50) were prehypertensive and 7.6% (n=41) were hypertensive. Conclusion: the sum of skinfolds were directly related to the systemic blood pressure of the adolescents assessed. doi:10.5020/18061230.2014.p263